An experiment on the winter demand commitment bargaining mechanism - Michela Chessa; Nobuyuki Hanaki; Aymeric Lardon; Takashi Yamada (Osaka University, Institute of Social and Economic Research (ISER), 2021)
In this paper we experimentally compare three implementations of Winter demand commitment bargaining mechanism: a one-period implementation, a twoperiod implementation with low and with high delay costs. Despite the different theoretical predictions, our results show that the three different implementations result in similar outcomes in all our domains of investigation, namely: coalition formation, alignment with the Shapley value prediction and axioms satisfaction. Our results suggest that a lighter bargaining implementation with only one period is often sufficient in providing allocations that sustain the Shapley value as appropriate cooperative solution concept, while saving unnecessary costs in terms of time and resources.
Keywords: C71; C72; C90; D82; 330; Nash Program; Shapley value; Experiments; Winter mechanism